Epidemiological, Morphological, and Histopathological Study of Quail Coccidiosis in Thi-Qar Province, Iraq - Al-Zarkoushi, Muntadher M F; Al-Zubaidi, Mohammed Th S (The Iraqi Journal of Veterinary Medicine, 2021)
Coccidiosis is the most common and important disease of poultry resulting in great economic losses world widely. The objective of this study was to define the species of Eimeria, their prevalence, and gut histopathological lesions in quails (Coturnix coturnix japonica) in Thi-Qar province, Iraq. Over the period of ten months (December 2019 to September 2020), a total of 330 fresh fecal samples (201 from males and 129 from females) were collected from different marketplaces and farms in Thi-Qar province. Direct smear and flotation techniques were used to examine the presence of Eimeria oocysts in the fecal samples. The sporulated oocyst shape indices were measured microscopically. Hematoxylin and eosin, as well as Periodic-Acid Schiff stains were used to diagnose potential pathological lesions and Eimeria developmental phases within the small (duodenum, jejunum, and ileum) and large (caeca) intestines. Four species, according to the criteria adopted, Eimeria bateri, Eimeria uzura, Eimeria tsunodai, and Eimeria fluminensis were uncovered in current study, with shape indices of 1.30, 1.36, 1.30, and 1.05, respectively. The total infection rate was 64.54%; and the morphological characteristics of the oocysts was identified. The highest infection rate was in E. bateri (41.78%), while the lowest infection rate was in E. fluminensis (7.98%). The highest prevalence rate was in March 84.84% with a significant effect at P<0.01. The sex of quail had no significant effect of the coccidiosis infection. The study revealed a destruction in the epithelium of the mucosa and submucosa of the intestine and development of the Eimeria stages, which led to malabsorption and consequently weight loss and economic losses in the quail industry.